2016
DOI: 10.1007/s11366-016-9419-x
|View full text |Cite
|
Sign up to set email alerts
|

Defending China’s National Image and ‘Defensive Soft Power’: the Case of Hong Kong’s ‘Umbrella Revolution’

Abstract: This study examines the pro-democracy protests of Hong Kong in 2014 and how the protests became sites for Beijing's representations of Chinese national image(s). It argues that 'defensive soft power' can be used to understand the process through which Beijing made such representations and projections. 'Defensive soft power', extending on Nye's soft power is operationally defined as the reactionary activities taken in response to actions that harm or potentially harm a country's national image. Based on an anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…In both defensive denial and charm offensive, ‘China’ is the explicit object of such discursive constructions. Concerned with ‘telling China’s stories’, both strategies are defensive in nature (Cao, 2014: 181; Loh, 2017; Sun, 2015).…”
Section: A Typology Of Media Discursive Practices In Soft-power Constmentioning
confidence: 99%
“…In both defensive denial and charm offensive, ‘China’ is the explicit object of such discursive constructions. Concerned with ‘telling China’s stories’, both strategies are defensive in nature (Cao, 2014: 181; Loh, 2017; Sun, 2015).…”
Section: A Typology Of Media Discursive Practices In Soft-power Constmentioning
confidence: 99%
“…The notion of soft power within the Chinese context is, indeed, somewhat different from what is usually accepted within the Western sphere, as it incorporates the concept of subduing an enemy without having to fight (Wang and Lu 2008). So, some have suggested that China is using soft power in a defensive manner by making a conscious effort to engage with and refute attacks made on China's image, while at the same time ensuring that the press also runs "ambivalent" articles about China so as to give the impression that the coverage is balanced (Loh 2017). China has also been seen as yielding "negative" soft power: instead of using soft power as a foreign policy tool, Beijing is actually more concerned about domestic policies and regime legitimacy (Callahan 2015).…”
Section: Harder Ways To Consider Soft Power? Soft Balancing and Defenmentioning
confidence: 98%
“…Ernest Wilson reunifies various strands of power, especially the hard and soft varieties, by defining smart power as "the capacity of an actor to combine elements of hard power and soft power in ways that are mutually reinforcing such that the actor's purposes are advanced effectively and efficiently" (2008,110). It then becomes imperative to consider more refined interpretations of soft power, and especially interpretations that depart from the view that all usage of soft power is "positive" and for the greater good, peace and harmony (Loh 2017). Recent works that consider soft power as defensive power, soft power as image shifting and soft power as niche diplomacy represent new articulations particularly helpful to the study of the North Korean case.…”
Section: Refined Usagementioning
confidence: 99%
See 2 more Smart Citations